Darkside - Becker, Tom 1981 (New York Orchard Books, 2008)
when, while running away from kidnappers, he stumbles upon Darkside, a terrifying and hidden part of London ruled by the descendants of Jack the Ripper, where Jonathan is in mortal danger if he cannot find the way out
Hurg
5 8
Keywords: England -- Juvenile fiction; Paranormal fiction